TRACING HERITAGE: ANALYZING MONTAGNOLA SENESE DRY STONE WALLS AS LINEAR REMNANTS OF HISTORICAL LAND MANAGEMENT - Paolo Bonavita (American Journal Of Agriculture And Horticulture Innovations, 2023)
This study presents a comprehensive methodological approach for analyzing the Montagnola Senese dry stone walls as linear infrastructures that offer insights into historical land management practices. Dry stone walls are not merely physical structures but hold intrinsic cultural and ecological significance, reflecting past human interactions with the landscape. Employing a multidisciplinary framework, this research combines historical research, archaeological surveys, remote sensing, and geographic information systems (GIS) analysis to unravel the complexities of these walls as historical artifacts. By examining their spatial distribution, construction techniques, and contextual relationships, we unearth valuable information about the land use patterns, agricultural practices, and socio-economic dynamics of the Montagnola Senese region in times gone by. The findings not only enrich our understanding of the area's heritage but also offer lessons for sustainable land management strategies today.